Abnormal GRHL2 Methylation Confers Malignant Progression to Acute Leukemia. (9th July 2022) - Hua, Jing; Ma, Congcong; Wang, Chao Hui; Wang, Yan; Feng, Saran; Xiao, Taiwu; Zhu, ChuanSheng
Abstract : Purpose . Abnormal methylation of Grainyhead-like 2 (GRHL2) is associated with a substantial role in the malignant phenotype of tumor patients. Our present research is aimed at studying the abnormal expression of GRHL2 and the association of methylation in patients with acute leukemia and its relationship with prognosis. Materials and Methods . We used quantitative real-time polymerase chain reaction (qRT-PCR) for detecting the aberrant expression level of GRHL2 in 60 patients with acute leukemia and 60 normal controls. We analyzed the significant correlation between the expression level of GRHL2 with clinicopathological features and patients' prognosis in acute leukemia using the corresponding statistical methods. Secondly, we employed qRT-PCR and Western blotting to detect the mRNA and protein levels of GRHL2 in leukemia cell lines. Next, we used methylation-specific polymerase chain reaction (MSP) technology for detecting the methylation of GRHL2 in clinical samples with acute leukemia and cell lines. Then we investigated the demethylating effect of arsenic trioxide and 5-azacitidine on the mRNA and protein expression levels of GRHL2 in cell lines of acute leukemia. Finally, we studied the effects of arsenide trioxide and 5-azacitidine on the proliferation of leukemia cells and the TGF- β signaling pathway. Results . We found a lower level of GRHL2 expression not only in acute leukemia patients but also in cell lines when compared with normal controls. At the same time, the expression level of GRHL2 in patients with acute leukemia was significantly correlated with leukocyte count, platelet count, and cytogenetic risk grouping. In addition, the lower GRHL2 expression group showed a significantly lower overall survival rate in acute leukemia patients than that of patients with a higher GRHL2 expression group. Univariate and multivariate analyses revealed that the expression of GRHL2 is an independent risk factor in acute leukemia patients. The methylation level of the GRHL2 promoter region in acute leukemia patients and cell lines was significantly higher than the normal control group, and we found the elevated mRNA and protein levels of GRHL2 in acute leukemia cell lines after the use of the demethylation drug arsenic trioxide and 5-azacitidine. At the same time, arsenide trioxide and 5-azacitidine are associated with the inhibition of cellular proliferation of acute leukemia cells and also promote the elevated expression of TGF- β signaling pathway-linked proteins, including TGF- β, Smad2, Smad3, and Smad4. Conclusion . Increased expression and methylation level of GRHL2 are closely associated with the prognosis and malignant phenotype of acute leukemia patients and play an irreplaceable role in the occurrence and development of patients with acute leukemia.